Flying Camelot : the F-15, the F-16, and the weaponization of fighter pilot nostalgia - Hankins, Michael W., 1982- (Battlegrounds (Ithaca, N.Y.), 2021)
"A study of the influence of fighter pilot culture and the technological development of the F-15 Eagle and F-16 Fighting Falcon fighter aircraft and the ensuing debates surrounding national defense strategy in the 1970s and 1980s"--